Transitioning Role of Parents in Binge Drinking in the Context of Alcohol Abstinent Religiosity Among Christian College Students - Baltazar, Alina M. (Journal of research on christian education, 2020)
College students transition from the parental home environment to the college environment. This study examined the transitioning role of parent/child relationships and religiosity in Christian college student heavy episodic drinking (HED). Analysis was conducted using data from a health-risk behavior survey administered on campus, n = 434. Believing the body is the temple of God was the only statistically significant variable in the logistic regression model, 78% less likely to engage in HED. These results show there is a transitioning role of parents during the college years with parents having less influence on HED than religious belief on a Christian college campus.